Speed Control Based on the Intelligent PID Algorithm for Robotic Fish - Jiang, Yu Lian; Ren, Ye Tong; Geng, Rui Zhi; Xue, Cui Wei (Applied Mechanics and Materials, 2013)
This Paper Provides a Speedcontrolling Method Based on the Intelligent PID Algorithm for Robotic Fish. by this Method, we can get the Appropriate Speed at Every Moment during the Robotic Fish Moving from Current Position to the Destination. Using it, we can Design and Optimize the Strategy when the Robotic Fish Head the Ball to the Target Point. Besides, we did many Experiments on Urwpgsimd Simulator Platform Using PID and Intelligent PID Algorithm Respectively. Variablecontrolling Approach is Applied to this Comparison. Lastly, the Result Shows that Robotic Fish can Head the Ball more Quickly and Steadily Using Intelligent PID Algorithm. And many Problems, such as Dropping the Ball and Deviating from the Target Point, are Avoided.